Transfer of Ownership Rights to Land as the Object of Sale and Purchase Under Hand (Receipt) (Study of Land Dispute Decision Number 49/Pdt.G/2025 at the Bitung District Court) - Rosyidah, Masfufah; Handayani, Sri Wahyu (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Land-related disputes in Indonesia frequently arise from specific parcels that become the source of conflicts concerning ownership rights and their utilization. This study aims to provide an in-depth analysis of the legal mechanisms governing the transfer of land ownership and the validity of land sale and purchase transactions conducted solely through receipts or private agreements. The research adopts a normative juridical method with a qualitative approach, combining the analysis of statutory regulations, a review of Bitung District Court Decision Number 49/Pdt.G/2025, and an extensive literature study. Data were obtained from primary, secondary, and tertiary legal sources, including statutes, case law, books, and scholarly journals. The findings reveal that the transfer of land ownership is closely linked to the validity of sale and purchase transactions conducted under private agreements. Although such transactions remain legally binding as civil agreements, they are administratively incomplete, thereby preventing the issuance of ownership certificates without additional procedures. These results underscore the necessity for diligence among parties involved and the critical role of Land Deed Officials (PPAT) in drafting authentic deeds. Ensuring compliance with these legal requirements enhances legal certainty, facilitates land registration, and helps prevent recurring land disputes.